Internal Audit Function and Board of Commissioners on Financial Performance With Institutional Ownership As A Moderation Variable (Study of Companies in the Financial Sector Listed on the Indonesia Stock Exchange for the Period 2020-2022) - Dwi Christina, Vinda; Lenggogeni, Lenggogeni (Dinasti Publisher, 2024)
This study aims to examine the relationship between internal audit functions and the board of commissioners on financial performance with institutional ownership as a moderating variable. The research method involved all public banking sector companies listed on the Indonesia Stock Exchange during the period from 2020 to 2022, collecting 51 company-year observations. Based on the analysis of previous research results, it is shown that the internal audit function and the board of commissioners have a negative impact on the financial performance of the company. These findings indicate that the role of internal audit functions and boards of commissioners in providing value-added services related to financial performance in Indonesian public companies is relatively small. This research is expected to enhance the understanding of the roles of internal audit functions and boards of commissioners and to encourage the practice of internal audit functions in public financial sector companies in Indonesia to improve financial performance in their consultative roles, especially regarding ROA performance.